Challenges and opportunities of tourism industry in Bangladesh - Zakaria, Lincoln (2011)
This project paper analyzed the challenges and opportunities to the Bangladeshi tourist sector focusing on its general status and development potential. Due to historical isolation Bangladeshi culture and history is distinct. The six national divisions offer both individually and combining a variety of natural and cultural destinations suitable for tourist attractions. The Bangladeshi authorities are concemed with safeguarding its heritage, including an extraordinary intangible heritage and the traditional Bengali handicraft Target groups in the Bangladesh tourism industry are: inbound tourists; the local high and middle class and expats. Bangladesh is one of the countries in the South Asian region that has the least arrivals and revenue eamed from the tourism industry. This might change in the future as the travel and tourism activity is forecast to increase worldwide, regionally and nationally. The tourism industry is quite a young line of business in Bangladesh. It is predominantly developed by local market forces to the national tourist market and a foreign urban business market. Organizations represent the govemment and private tourist sector, but co-operation, strategies and policies to develop a prosperous and sustainable tourist industry are rear. Both local and intemational tourist players are competing for the existing market, but no Bangladeshi tour operator works abroad, and no foreign tour operator work in Bangladesh. To successfully develop the Bangladeshi tourism industry a local based strategy is crucial. This strategy should aim both at sustainable development (including economical, cultural and environmental considerations) and increasing tourist income. lt is obvious to focus on existing local markets as well as to aim for the traditionally proﬁtable inbound tourist market.